Uvajanje sprememb v operacijskih dvoranah - ekološka, organizacijska, kadrovska in ekonomska izhodišča - Peric, Helena (Obzornik zdravstvene nege, 2002)
Medical devices, manufactured for the purpose of draping patient and protective clothing of operating theatre staff; should be used in the operating theatres. Cotton materials are used mostly in Slovenian hospitals, which is professionally and legally disputable. Implementation of medical devices in the place of disputable cotton materials is demanding project that needs to address ecological, organisational, human resources and economical issues. Ecological issues relate to the life cycle assessments of the productsand not only to waste disposal. Sufficient knowledge of present and future organisational processes is needed in order to implement changes successfully. Changes in organisational process lead to changes in human resources area-efficient problem solving in this area depends on application of human resources development in each institution. Use of professionally acceptable materials leads to less risk for postoperative infections, which means less pain and suffering for patients and also less cost for institution and society. Foreign and national cost calculation show savings with use of single use medical devices-nevertheless we should remember that professionallyand legally disputable material is compared to professionally and legally acceptable one.
Keywords: Bombaž; Cotton; Economics; health care; Medical waste; Medicinski odpadki; operacijska soba; Operacijska soba, nega; Operating room nursing; organizacija; organization; Organization and administration; zdravstvena nega; zdravstvo